Genetic variants in RIG-I-like receptor influences HCV clearance in Chinese Han population. (2019) - Wu, Xinyu; Zang, Feng; Liu, Mei; Zhuo, Lingyun; Wu, Jingjing; Xia, Xueshan; Feng, Yue; Yu, Rongbin; Huang, Peng; Yang, Sheng
Abstract: Human innate immune plays an essential role in the spontaneous clearance of acute infection and therapy of HCV. We investigated whether the SNPs in retinoic acid-inducible gene I-like receptor family were associated with HCV spontaneous clearance and response to treatment. To evaluate the clinical value of DDX58 rs3824456, rs10813831 and rs10738889 genotypes on HCV spontaneous clearance and treatment response in Chinese Han population, we genotyped 1001 HCV persistent infectors, 599 participants with HCV natural clearance and 354 patients with PEGylated interferon- α and ribavirin (PEG IFN- α /RBV) treatment. People carrying rs10813831-G allele genotype were more liable to achieve spontaneous clearance than the carriage of the T allele (dominant model: adjusted OR 1.35, 95% CI 1.08–1.71, P = 0.008). In rs10738889, the rate of persistent infection was significantly lower in patients with the TC genotype compared to those with TT genotype (dominant model: adjusted OR 1.36, 95% CI 1.06–1.74, P = 0.015). Multivariate stepwise analysis indicated that rs10738889, age, alanine aminotransferase (ALT) and aspartate aminotransferase (AST) were independent predictors for HCV spontaneous clearance. However, there were no significant differences in the three selection SNPs between the non-SVR group and the SVR group. These results suggest the DDX58 rs10813831 and rs10738889 are associated with spontaneous clearance of HCV, which may be identified as a predictive marker in the Chinese Han population of HCV.